2016
DOI: 10.12740/pp/36316
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes and aggression in the Emo subculture

Abstract: In the Emo subculture, teenagers'aggressive behaviour is related to improper parental attitudes. It has been stated that mother's attitudes, irrespective of subculture, are much more strongly associated with the aggression among adolescents than father's attitudes. Moreover, aggressive behaviour in the Emo subculture occurs when father displays an excessively demanding attitude. A reduction of the level of almost all kinds of aggression manifested among teenagers from the Emo subculture is associated with moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Published by Francis Academic Press, UK -220-shown to have a negative impact on one's psychosocial adaptation. Research has found that emo subcultural participants showed more aggressive behaviors [6] , and that emotions were related to suicidal thoughts, extreme loneliness, and self-injurious behaviors [ 7 ] .A study found that found that a high incidence of suicide, depression, and self-injurious behaviors was related to goth emotional subcultural participation and identification [8] . Furthermore, Another study showed that young people identifying with goth subculture might be at increased risk for depression and self-harm [9] .Therefore, further indepth research on emo subcultures will be significant both for enriching the field of youth subcultures and for realistic youth education guidance and work practices.…”
Section: Youth Subculture and Emo Subculturementioning
confidence: 99%
“…Published by Francis Academic Press, UK -220-shown to have a negative impact on one's psychosocial adaptation. Research has found that emo subcultural participants showed more aggressive behaviors [6] , and that emotions were related to suicidal thoughts, extreme loneliness, and self-injurious behaviors [ 7 ] .A study found that found that a high incidence of suicide, depression, and self-injurious behaviors was related to goth emotional subcultural participation and identification [8] . Furthermore, Another study showed that young people identifying with goth subculture might be at increased risk for depression and self-harm [9] .Therefore, further indepth research on emo subcultures will be significant both for enriching the field of youth subcultures and for realistic youth education guidance and work practices.…”
Section: Youth Subculture and Emo Subculturementioning
confidence: 99%
“…In aforementioned section, emo is both music genre and subculture, some members or fans of which engage self-mutilation and suicide, while public stereotyped them -as a whole-to be folk devils with aggression against self [30], [31]. Problem music, whether punk, emo, or metal, has been targeted as the cause of negative behaviors [32].…”
Section: Hypotheses Constructionmentioning
confidence: 99%